Determining optimal handball player rates of body size: A phantom alternative? - Massuca, L.; Fragoso, I. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
A range of relevant anthropometric factors can be considered which are subject to strong genetic influences (e.g. stature) or are largely environmentally determined and susceptible to training effects (see Reilly, Bangsbo and Franks, 2000). However, in the throwing events like handball, the anthropometric profile of elite players is first based in height and weight, followed by span and hand measures (Blanco, 2004). The aim of the current study were (i) to make a conditional characterization and to describe the relation between height and weight of male handball players of different levels, (ii) to assess its ability to distinguish different level adult players and (iii) to test Phantom and Lentini Combined Methods: 561 male handball players (WC 2007, n = 395; LPA 2007-08, n = 184) were studied (mean age = 25.99 years, s = 4.64; height = 188.46 cm, s = 7.11; body mass = 89.07 kg, s = 9.97). WC 2007 was classed as those who had participated in the XXTH Men`s Handball World Championship 2007 (in Germany). LPA 2007-08 players were classed as those who were signed for a Portuguese Professional Handball Club in season 2007-08. Two anthropometric measurements for each participant were taken during year 2007. These included height and body mass. To study the sportsmen proportionality were used (i) height and weight relation, (ii) body mass index, (iii) optimal weight, (iv) Phantom Method and (v) Lentini Combined Method. Statistical analysis involved variables description, though mean and standard deviation. The t-test for equality of means was performed to compare level groups (Independent Sample Test) and to compare results of Phantom and Lentini Methods (Paired Sample Test). For all analyses, 5% was adopted as the significance level and analyses were carried out with SPSS (Statistical Package for the Social Sciences) 15.0 software for Windows. The results showed: (i) significant difference in body size (height and weight, all p < 0.01) and no significant differences in body mass index and optimal weight (all p > 0.05) variables between groups, (ii) significant difference between groups in Phantom Z value of height (p < 0.01) and no significant differences when considered the Phantom Z value of weight (p > 0.05), (iii) that Lentini combined method normalize the data pulling the results to the mean Z value (height and weight, all p < 0.01) comparing with Phantom method, and allows similar statistical results than original data. The results suggest that the use of Lentini combined method seems to be useful to study the sportsmen proportionality, and the body size of handball players participated in the XXTH Men`s Handball World Championship 2007 (mean height = 189.13 cm, s = 7.20; body mass = 90.05 kg, s = 9.60) can be used as male reference data.